Identification of a new group of Chlamydia psittaci strains called TWAR. - Kuo, C C (1986)
A new group of Chlamydia psittaci strains has been identified. They are called TWAR after the laboratory designation of the first two isolates. Twelve strains were isolated from pharyngeal swabs of different persons with acute respiratory disease in Seattle, Wash., during 1983 to 1986. One strain was obtained from the eye of a child during the trachoma vaccine study in Taiwan in 1965. Nine strains were characterized in this study. TWAR organisms formed intracytoplasmic inclusions in HeLa cells which were morphologically typical of C. psittaci and iodine stain negative (contained no glycogen). Immunological analysis with various chlamydia-specific monoclonal antibodies revealed that TWAR strains belong to the genus Chlamydia, are distinct from C. trachomatis, and are serologically unique among C. psittaci. All TWAR strains so far isolated appear identical serologically. TWAR organisms grew poorly in egg and cell cultures and demonstrated low virulence to mice by intracerebral, intranasal, and intravenous inoculation. Available data suggest that the TWAR strain is a primary human pathogen.